Leaf Extract of Cassia fistula: A Biofungicide against Colletotrichum gloeosporioides and Cercospora bataticola - Doomar Singh; Sushil Kumar Yadav; Santosh Kumar (Cutting Edge Research in Biology Vol. 1, 2022)
Indiscriminate and uncontrolled use of chemical fungicides have developed resistant in many fungal plant pathogens which challenging to control most fungal plant diseases. Since the dawn of time, phytochemicals have contributed a significant role to human welfare without causing any harm. PFT method with different leaf extracts of Cassia fistula (Aqueous, methanol and acetone) and their three concentrations (250\(μ\)l, 500\(μ\)l and 1000\(μ\)l per 15 ml of PDA) were used against Colletotrichum gloeosporioides causing anthracnose (a post-harvest disease of fruits) and Cercospora bataticola, causing leaf spot of beet. The study’s findings revealed that maximum inhibition (76.8%) of Colletotrichum gloeosporioides was found with1000\(μ\)l concentration of methanolic extract of Cassia fistula leaves 3 DAI while maximum inhibition of Cercospora bataticola (68.7%) was found with the same concentration of acetone extract of Cassia fistula leaves 3 DAI. Considerable growth inhibition of Colletotrichum gloeosporioides (68.7%) and Cercospora bataticola (50.5%) were found with 1000\(μ\)l concentration of methanolic and acetonic extracts of Cassia fistula leaves. 5 DAI. Acetonic extract of Cassia fistula leaves with 1000\(μ\)l concentration was also found as a good antifungal for Colletotrichum gloeosporioides with 64.8% and 54.6% growth inhibition 3 DAI and 5 DAI respectively. The current study found that methanolic and acetonic leaf extracts of Cassia fistula can be used for fungal plant disease management, but more research is needed.